SENDERIZACIÓN Y SEÑALETICA DE LA CICLO RUTA TURÍSTICA EL MIRADOR LA CRUZ DE LA CIUDAD DE CATAMAYO CANTÓN CATAMAYO PROVINCIA DE LOJA - MENDOZA DIAZ, ISAMAR CAROLINA (2017)
The Catamayo canton is the largest and fertile of the lojanos valleys, with inexhaustible riches that call to be explored, known and exploited; The hospitality and the simplicity of its people make of this valley a place of great attraction for the tourists. The present research work refers to the "Senderization and Signaltics of the Tourist Route Cycle The lookout the cross of the City of Catamayo, Catamayo Canton, Province of Loja." It is based on highlighting and taking advantage of its characteristics and all tourist resources of its Neighborhoods, so that in this way it becomes a tourist product of quality and at the same time generate economic resources to this canton. The name of the path lookout the cross is due to the fact that from the beginning and along the route you can observe in a panoramic way the Catamayo valley, enjoy the aroma of cane and the service of its people, Catamayo is a valley that From any point of view you can see the monument of the lookout the cross, as emblematic axis of the religious devotion of its inhabitants. It was determined objectives that are in line with the theme set out a general objective and three specific in which it is written below: The general objective is the "Study of a Proposal of Senderization and Signal of the Cycle Tourist Route lookout the crossde la ciudad de Catamayo, Province of Loja. "For this purpose, three specific objectives were formulated: To make a diagnosis of the current situation of the tourist attractions that are part of the tourist route cycle lookout the cross in the city of Catamayo; To design a proposal of Senderización and signage of the Ciclo tourist route The Mirador The Cross of the city of Catamayo of the Catamayo Province of Loja; Identify potential significant environmental impacts that may occur throughout the project phase. In the methodological of the Senderization and Signaltics of the Tourism Route Cycle The lookout the cross, a critical scientific reading was made, for the construction of the conceptual framework and reference frame, for the development of each one of the objectives was necessary to employ methodologies between them The analytical, synthetic, inductive and deductive method and appropriate techniques in which direct observation, interview and rapid analysis methodology and participatory planning are mentioned. The first objective was to make a diagnosis of the current situation regarding services, infrastructure, characteristics of attractions and neighborhoods that are part of the cycle route referring to a preliminary SWOT analysis, with visits And interviews with key informants carried out on site and field research technique, where it has been verified that at present this route is devalued by the small importance and motivation to carry out the cycling activity. For the second specific objective, a proposal was made to contribute to the tourist development of the Catamayo canton in which a proposal was designed, evaluated and executed based on the SWOT analysis, with the aim of improving and correcting the shortcomings that exist in the canton Catamayo, creating a model of directional, ornamental, restrictive signage, pictograms of support services, tourist activity, natural attractions and a totems for the lookout the cross Route Cycle, for which the Tourist Signage Manual facilitated by the Ministry of Tourism of the City of Loja in order to improve tourist development in addition to placing a logo to the cycle route and to promote it through a triptych. For the fulfillment of the third objective To identify the possible environmental impacts, the qualitative and environmental impact matrices that came up in the implementation of the project were carried out. With respect to the results obtained it is deduced that it is vitally important to carry out the Senderización and Señalética of the Cycle Touristic Route lookout the cross as it would be an attraction that gathers the characteristics, customs and traditions necessary to motivate the visitors that make the route Of the same and to encourage the practice of tourist cycling. Concluding that in the city of Catamayo there are a variety of important tourist attractions, which need to be adequate and enhanced by the different authorities that are in charge, the lack of signage in these places prevents the tourist can be guided and enjoy an environment Welcoming and carry out activities of leisure and fun through the route cycle therefore the proposal of signage arises to contribute in a positive way to the different attractions of the city of Catamayo. As recommendations especially requested the Catamayo GAD work together with MITUR on tourism projects that strengthen the tourism activities of different visitors integrating the rural sectors of the different cantons. Finally, to manage with the competent authorities to carry out the execution of the project and to